Проблемот на недефинирливоста на светото во теориите за религијата - Тодоровска, Марија (Меѓународен Центар за Славјанска Просвета - Свети Николе, 2015)
The dedicated care towards the object of religious belief that homo religiosus exhibits, and the complex phenomena and relations of religious faith are not quantifiable, subject to scientific scrutiny, conceivable in rational terms or effable. The diverse and interdisciplinary perspectives of the theories of religion, and especially of the theories of the sacred face problems of undefinability of the holy experience, of subjectivity of the parameters of belief and of the methodological dissonance between theory and the transcendent realm beyond the cognitive possibilities of rational categories it is trying to encompass and analyse. The text briefly overviews the relationship between science and religion through notions of rational knowledge and (irrational) faith, shown mostly in examples of primordial religious belief. Principles of sympathetic magic are compared to rudimentary science with flawed laws of association. The sacred-profane dichotomy in animatism, totemism and early religion in general, while crucial to the preservation of the cosmos of the believer, is shown to be difficult to narrow down in theoretical terms, due partly to their reciprocal codependence, and partly to the fact that the realm of the sacred transcends the realm of the profane, where theoretical insight is undoubtedly rooted. The problem of ineffability of the numinous experience is briefly tackled as an issue not only of the limitations of language and rationality, but also of meta-approaches to faith and knowledge.
The problem of undefinability of the sacres in theories of religion
Keywords: sacred, religion, faith, mana, numinous, definition